Optical Response Study of the Al/a-Sic:H Schottky Diode for Different Substrate Temperatures of the R.F. Sputtered a-Sic:H Thin Film - L. Magafas (Active and Passive Electronic Components)
In the present work, Schottky diodes of Al/a-SiC:H included in the structure Al/a-SiC:H/c-Si(n)/Al were fabricated and their optical response was studied in the wavelength region from 350 nm up to 1000 nm, for different substrate temperatures, Ts (from 30°C up to 290°C) of the r.f. sputtered a-SiC:H thin film. The spectral response of these structures exhibits two maximum values of quantum efficiency. The first maximum is presented at wavelength λ≅525 nm and the other at λ=850 850 nm, which are attributed to the Aa-SiC:H Schottky junction and the a-SiC:H/c-Si(n) isotype heterojunction, respectively. The position of the first maximum owing to the Al/a-SiC:H junction as well as the values of quantum efficiency, for the range of wavelengths from 350 nm up to 700 nm, depends on the substrate temperature, Ts, of the a-SiC:H thin film. In the case that Ts is 120°C, the spectral response of the Al/a-SiC:H/c-Si(n)/Al structure for a reverse bias voltage V = -2V exhibits high values of quantum efficiency (up to 40%) with slight variation in the range of wavelength from 475 nm up to 925 nm, making this structure interesting as a wide band optical sensor device. Finally, the minority carrier (holes) diffusion length of a-SiC:H for TS=120°C was calculated and it was found to be ≅2.200 Å.